The eLuna mixed-reality visual language for co-design of narrative game-based learning trails - Breien, Fredrik; Wasson, Barbara; Greiff, Samuel; Hauan, Nils Petter (Frontiers in Education, 2022)
Increased focus on out-of-school learning has led to extended use of Science Centers as learning arenas, particularly by junior and high school students in formal learning situations. The creation of learning trails, semantic collections of science center exhibits based on formal learning plans for interdisciplinary STEAM education, has become a focus area in large parts of the world. Grounded design research has resulted in the definition of story-driven learning trails that foster flow and engagement in learners. In science centers, equal emphasis is placed on the physical real-world domain, represented by the exhibits themselves, as the virtual components, represented as collaborative positions-based portables carried between exhibits, linking the exhibits into virtual storylines using sensors and control assignments. This defines science center learning trails as mixed reality systems; holistic systems that integrate real and virtual elements, existing on the axis between real and virtual poles on the reality-virtuality continuum. Research has shown that a particular set of characteristics of narrative game-based learning has positive effects on engagement, motivation, and learning. The eLuna Framework comprises a co-design method and a visual language that emphasizes these characteristics, and that supports educators and game developers to co-specify blueprints of screen-based narrative learning game experiences. To achieve its full potential to co-design and co-specify science center learning trails, the eLuna Visual Language needs to be extended to distinguish real and virtual elements from one another in the resulting blueprints. Data from two design studies completed by six science center educators based on a STEAM enabled exhibit cluster at the Bergen Science Centre VilVite and a subsequent heuristic evaluation of the visual language output by eight evaluators has resulted in the eLuna Mixed Reality Visual Language. This research extends the eLuna Visual Language with Mixed Reality capabilities that can be plugged into the method and applied in future co-design and co-specification of mixed-reality narrative game-based learning trails which promote flow in learners, and affords positive effects on engagement, motivation, and learning.